Psychosocial Well-Being and HIV-Related Immune Health Outcomes among HIV-Positive Older Adults: Support for a Biopsychosocial Model of HIV Stigma and Health. (2nd December 2019) - Rendina, H. Jonathon; Weaver, Laurel; Millar, Brett M.; López-Matos, Jonathan; Parsons, Jeffrey T.
Evidence suggests that psychosocial stress negatively impacts immunological health in HIV-positive individuals. However, few studies have explored this association in substance-using older adults living with HIV (OALWH). We evaluated the effect of depression, loneliness, substance use problems, and HIV stigma on primary markers of immune function in a sample of 120 OALWH with substance-related issues. HIV stigma correlated with the greatest number of factors, including depression, loneliness, and substance use problems. Older age and antiretroviral adherence were associated with viral suppression, which was in turn associated with higher percentage of CD4 count. Multivariate path analyses demonstrated that lower HIV stigma and viral suppression were the only factors independently associated with higher percentage of CD4 count, with a significant indirect effect of adherence on CD4 through viral suppression. HIV stigma emerged as the most salient factor associated with both psychosocial well-being and immune health in the current study, suggesting that it is a critical factor to consider in future interventions for the rapidly growing population of OALWH.